Oil Exploration Economics: Empirical Evidence from Indonesian Geological Basins - Patria, Hari; Adrison, Vid (UI Scholars Hub, 2015)
Oil exploration has been subject to economic research for decades. Earlier studies of exploration models are mostly discussed the behavior of exploration at the macro-level analysis such as field, firm, region, and continental. This paper then focuses on the geological and economic factors that determine the well-drilling decision at the micro-level using disaggregated panel data of 32 geological basins in Indonesia over the period of 2004-2013. This study shows that the number of drilled wells is determined significantly by the lag of success rate, lag of discovery size, lag of global oil price, and regional location of geological basin.